The pillars of finance : the misalignment of finance theory and investment practice - Fraser-Sampson, Guy; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Written by bestselling finance author Guy Fraser-Sampson, this is a provocative account of the severe limitations of modern finance, advocating a bold new way forward for the finance industry. The Pillars of Finance is a lively and provocative read, challenging some of the core beliefs of modern finance.
Keywords: Finance; Business enterprises -- Finance; Business mathematics; Investment banking; Securities; Risk management; Economic history